G20, Infrastructure Tourism, and Renewable Energy Tourism - Muhammad Ikhsan Setiawan; Agus Sukoco; Dahlan Abdullah; Cut Ita Erliana; Paisal Halim; Syamsiah Badruddin; Hery Budiyanto (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
The tourism industry has made an enormous difference in terms of jobs, foreign exchange, and the building up of infrastructure. On the other hand, many infrastructures can make natural places look less attractive, which calls for sustainable tourism. It's vital to help small businesses get money through excellent digital infrastructure and to use public fiscal tools to ensure that natural resources are used sustainably. Infrastructure tourism was used as the title, abstract, and keywords in 6,377 documents from 1968 to 2023 found in the scopus.com database. It also shows 704 papers with the title, abstract, and article keyword "Renewable Energy Tourism" from 1990 to 2022. Based on research papers on scopus.com, Indonesia is ranked second in Asia for renewable energy tourism and first in ASEAN for infrastructure tourism. It's a perfect sign for the growth of tourism infrastructure and renewable energy tourism in Indonesia. Indonesia has many affiliations, including the University of Indonesia, the Bandung Institute of Technology, Gadjah Mada University, Bina Nusantara University, Diponegoro University, Brawijaya University, IPB University, Padjadjaran University, and Hasanuddin University. Research publications in Indonesia have received funding from the Ministry of Technology Research, the Directorate General of Higher Education, the Research and Service Institute, the Bandung Institute of Technology, the University of Indonesia, Airlangga University, and Diponegoro University. So, the infrastructure and Renewable Energy Tourism research are on track and in an excellent place to be published. Indonesia will lead the world.